STRATEGI PEDAGANG MENGHADAPI PERSAINGAN (STUDI KASUS WARUNG SEMBAKO PAK RAHMAD DI DEPOK) - Arif, Arif Muhammad (Fakultas Ekonomi Universitas IBA, 2021)
This study aims to find out more about the management of the basic food stall business so that it can compete with other basic food stalls. The method used in this research is a qualitative and quantitative analysis method. Qualitative analysis is used to determine the management process using management functions (Planning, Organizing, Actuating, Controlling), and quantitative analysis using the calculation of Cash Flow, Break Even Point (BEP), Payback Period, and B/C Ratio (Benefit Cost Ratio). ). From the results of the calculation of the financial aspect, it can be seen that the profit of Mr. Rahmad's food stall business using cash flow calculations is Rp. 7,670,000 per month, while the payback period is 4 months, the return on investment is acceptable. The calculation of the unit BEP is 143.36 kg. Meanwhile, the rupiah unit BEP is Rp. 3,442,959. According to the calculation of the Benefit Cash Ratio of 18.4 > 1, Pak Rahmad's basic food stall is feasible.